2021
DOI: 10.1016/j.mtla.2020.100989
|View full text |Cite
|
Sign up to set email alerts
|

Flash oxidation tests to evidence the segregation of boron at the grain boundaries of superalloy Inconel 718

Abstract: In this study very short oxidation tests, called flash oxidation tests, were carried out at high temperature on samples of superalloy Inconel 718 containing some boron. Following these tests, a specific oxidation pattern was evidenced: spots were observed on the oxide film, these spots being discontinuously distributed along the grain boundaries. Whether outside or inside the spots, the oxide film exhibited the same three oxide layers which were likely rutile oxide (Cr,Nb,Ti)0 2 , chromia oxide Cr 2 O 3 and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Binder et al [27] evidence that the increase of boron concentration in Cr–Ni–Co–Fe alloys accelerates the development of complex spinels at the protective oxide Cr 2 O 3 , improving the corrosion resistance. Vernier et al [28] found boron atoms – initially in the solid solution in the matrix – incorporated in the protective oxide layer of the Inconel 718. Besides, the literature presents that the addition of B in Ni–Cr superalloys can reduce the agglomeration of M23C6 carbides [29], diminishing the sensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…Binder et al [27] evidence that the increase of boron concentration in Cr–Ni–Co–Fe alloys accelerates the development of complex spinels at the protective oxide Cr 2 O 3 , improving the corrosion resistance. Vernier et al [28] found boron atoms – initially in the solid solution in the matrix – incorporated in the protective oxide layer of the Inconel 718. Besides, the literature presents that the addition of B in Ni–Cr superalloys can reduce the agglomeration of M23C6 carbides [29], diminishing the sensitisation.…”
Section: Discussionmentioning
confidence: 99%